Kontribusi Explosive Power Otot Tungkai Terhadap Hasil Lompat Jauh Gaya Jongkok Pada Mahasiswa Putra Prodi Pendidikan Kepelatihan Olahraga Semester II Universitas Riau - Slamet Slamet; Ali Mandan; Ardiah Juita; Ridwan Sinurat (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
This study is correlational research that aims to find the contribution of leg muscleexplosive power to yield long jump squat style. The student sample was the son of varsity sportscoaching education Riau semester totaling 42 people. As the independent variable is theexplosive power leg muscle while dependent variable is the result of the long jump jongok style.Data (x) obtained from the test results without the leading long jump (standing board jump) toassess leg muscle explosive power while data (y) obtained from testing the long jump squat styleusing the prefix. Data were analyzed with statistical normality test is a test last lilifors alsoanalyzed the data to look for the correlation coefficient, and then proceed to test "t" after itsought the contribution. From the results of data processing for the normal distribution of dataobtained for the provision of data (x) and abnormally distributed in terms of data (y). r = 0.32,then through the test "t", t_ (count>) ttabel then there is a significant relationship between theexplosive muscle power with the outcome long jump squat style, via analysis of leg muscleexplosive power of determination have contributed 10.24% and 89 , 76% was contributed byother factors.